Pengetahuan Mahasiswa Untirta terhadap Ecobrick sebagai Salah Satu Cara Pemanfaatan Sampah Plastik - Enggar Utari; Febryani Elisabeth; Annisa Hidayah (Jurnal Ekologi, Masyarakat dan Sains, 2023)
This study aims to determine the knowledge of Biology Education students at Sultan Ageng Tirtayasa (Untirta) related to plastic waste, the use of plastic waste, recycling, and students’ knowledge of ecobrick. The research wasconducted qualitatively with descriptive methode. The mehode uses data analysis techniques in the form of primary survey conducted with questionnaries and secondary survey with relevant literature studies. The target of research is the active students of Biology Education at Untirta. As many as 98% of respondents are agree that ecobrick can be a solution for handling unresolved plastic waste. Ecobrick is a way to use plastic waste easily, cheaply, and with economic value. The existence of waste utilization is expected to provide awareness for Biology Education students at Untirta in an effort to protect the environment and together overcome the waste problems.